AN ANALYSIS OF ANIMATION MOVIE “RATOTOUILLE” THAT REFLECTING THE POLITENESS OF OFF RECORD STRATEGIES - Risvia Yosi Kusumah; Acep Haryudin (IKIP Siliwangi, 2019)
The aims of this research is to know that using off record strategies, people can make a relation with other people. To communicate their ideas in social interaction, human beings frequently use an indirect expression. Whenever people want to communicate for a specific information or provide as much of that information as possible, they show to express it indirectly, so there is a gap between what is said and what is delivered, that kind of communication provide a small part of an account of how people can communicate well by using indirect language with other (Yanti, 2017). The writer choose title “An Analysis of Animation Movie ‘Ratotouille’ that Reflecting the Politeness of Off Record Strategies.” This movie tell about a rat named Remy dreams of becoming a great French chef despite his family’s whises and the obvious problem of being a rat in a decidedly rodent-phobic profession. The writter chooses qualitative method, using informal method (collecting data, analysing data, and presenting the result).